FOUR SYMPATRIC SPECIES OF THELASTOMATIDAE (NEMATODA) PARASITES OF AMERICAN COCKROACH PERIPLANETA AMERICANA (L.) (BLATTODEA, BLATTIDAE) IN LA PLATA, ARGENTINA - Camino, Nora B. (2012)
The study of nematodes of the American cockroach Periplaneta americana (L.) lies in the need to find some pathogen to control it. This insect contaminates food and carries bacteria, protozoa and viruses. Cockroach droppings contain a number of allergens that cause some people to have skin rashes, watery eyes, nasal congestion and asthma. The aim of this study was to record the nematode fauna in P. americana in Argentina. Nymphs of P. americana (n = 80) were collected from an abandoned house in the north of the city of La Plata (34 º 55'S and 57 º 57'W), Buenos Aires, Argentina during the springsummer 2010-2011. Cockroaches were collected by trap capture. The insects were dissected in Petri dishes with distilled water under a stereomicroscope. Half the nematodes found in the digestive tract were killed by placing them in distilled water at 60 ° C for two min, then placed in the solution and TAF 50% and water for 48 h and then in pure TAF. We found four sympatric species of oxyurid nematodes belonging to the family Thelastomatidae, that parasitized the intestine of P. americana. Blattophila sp. and Leidynema sp. with a 30% parasitism. Hammerschmidtiella sp. and Thelastoma domesticus Camino & Quelas, 2008, showed a prevalence of 45% and 25%, respectively, and were found in separate hosts.